2019
DOI: 10.1080/15384101.2019.1577666
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of the p53-p21 pathway by G2019S LRRK2 contributes to the cellular senescence and accumulation of α-synuclein

Abstract: Parkinson's disease (PD) is characterized by the degeneration of dopaminergic neurons in the substantia nigra and the presence of Lewy bodies (LB) in neurons. α-Synuclein (αSyn) is a major component of LB and promote the PD pathogenesis via its accumulation by the impaired proteasomal or autophagic clearance. Numerous studies have revealed that the reduction of proteasome activity and autophagy is accelerated by cellular senescence. Leucine-rich repeat kinase 2 (LRRK2) contributes to PD progression and its mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…P53 can mediate cell response to DNA damage, replicative aging due to telomere shortening, as well as stress-induced premature senescence. Its downstream factor p21 can inhibit CDK2 and CDK4, rendering them unable to phosphorylate pRB [19,20]. The resultant hypo-phosphorylated pRB can bind to E2F and prevent it from binding to target genes, thereby prohibiting cells from entering the S phase.…”
Section: Influence Of Curcumin On Cellular Senescencementioning
confidence: 99%
“…P53 can mediate cell response to DNA damage, replicative aging due to telomere shortening, as well as stress-induced premature senescence. Its downstream factor p21 can inhibit CDK2 and CDK4, rendering them unable to phosphorylate pRB [19,20]. The resultant hypo-phosphorylated pRB can bind to E2F and prevent it from binding to target genes, thereby prohibiting cells from entering the S phase.…”
Section: Influence Of Curcumin On Cellular Senescencementioning
confidence: 99%
“…Follow-up experiments to deplete microglia after Satb1 reduction would conclusively demonstrate whether or not Cdkn1a-expressing dopaminergic neurons fulfill the criterion of apoptosis resistance in neuronal senescence. Indeed, elevated p21 expression induced apoptosis in vitro, indicating that it may not confer neuronal apoptosis resistance [ 77 ]. Nevertheless, the study by Riessland et al determined a dopaminergic neuron-specific role of SATB1 in modulating Cdkn1a/p21 expression and downstream senescence phenotypes including karyomegaly, mitochondrial dysfunction, production of SASP, lysosomal dysfunction and presence of SA β-gal and lipofuscin [ 56 ].…”
Section: Neuronsmentioning
confidence: 99%
“…While many of these processes including those addressed above are thought to contribute to neuronal degeneration, some are also hypothesized to reflect survival-promoting mechanisms such as senescence. More recent studies focused on neuronal senescence in PD have revealed that overexpression of mutant p53, p21, or mutant Leucine-rich repeat kinase 2 (LRRK2) increased SA β-gal, and αSyn protein expression and fibril accumulation in vitro [ 77 ]. Transgenic mice expressing the same mutant LRRK2 G2019S displayed elevated oligomeric αSyn, β-galactosidase and p21 expression.…”
Section: Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…The generation of αSyn brils was described in our previous report (19). We transfected cells with 0.15 µg GFP or 1.0 µg GFP-NCL using LipoD293 for 24 h following the 6 h pre-treatment of 700 nM αSyn brils.…”
Section: Uptake Of αSyn Brilsmentioning
confidence: 99%